Development of a Parametric Life Cycle Assessment (LCA) method for Construction Logistics in a Circular Economy - Athamkavil, Sreelaj; Mohan, Mahesh (My University, 2025)
This thesis presents a parametric Life Cycle Assessment (LCA) model for evaluating the environmental impacts of construction logistics in circular economy contexts. The focus lies on quantifying the greenhouse gas emissions associated with transporting five categories of recovered construction material such as steel reinforcement bars, glass partitions, wooden doors, wooden flooring, and mineral wool in Sweden.Using openLCA 2.1 and the ecoinvent 3.8 database, logistics scenarios are modeled for diesel, biodiesel, and electric heavy goods vehicles. The analysis includes both single-load and co-loaded transport configurations. Results show that electric trucks, despite lower payload capacities, yield the lowest emissions due to the low-carbon Swedish electricity mix. Co-loading strategies also prove effective in reducing the total number of trips and overall emissions.Break-even distances are calculated to determine the threshold at which transporting reused materials becomes environmentally beneficial, with distances varying significantly by material and transport mode. An uncertainty analysis was performed to evaluate the sensitivity of break-even distances under different transport and loading conditions. The proposed model demonstrates the significance of logistics choices in circular construction planning. It offers practical insights for stakeholders aiming to reduce transport emissions and supports improved integration of logistics parameters into LCA frameworks.
Keywords: Construction logistics, circular economy, Life Cycle Assessment, greenhouse gas emissions, parametric modeling, transport strategies, breakeven distance, uncertainty analysis